Consignação em folha de pagamento : estudo sobre o papel da instituição nas implicações do uso da margem de consignação pelos servidores públicos - Rezende, Richard Cardoso de (2014)
The use of consignment margin is indicative factor of the employee plublic debt, because it jeopardizes part of your future income decreased their purchasing power. From the year 2003 the Brazilian government encouraged the payroll loan offer more attractive interest rates, leading and an increase in the balance of contracted operations 1340.20% from 2004 to 2011. Because the employment characteristics of the employee public became the main payroll borrowers. However, not understanding the margin of assignment and the lack of financial education can cause the employee public please state of financial difficulty, especially as over-indebtedness, which is the inability to pay their credit debts, may be reflected in the development of work. In order to achieve the objective of identifying the role of the institution about the implications of using the margin of consignment by civil employee, was conducted of survey with quantitative and qualitative approach through a questionnaire, yielding a return of 210 valid responses. Data were tabulated and analyzed using statistical techniques such as descriptive analysis and contingency tables watching the values of the chi-square test and Cramer's V. The findings indicate that the financial guidance employee public can help to use the consignment margin more consciously avoiding financial problems and improving their performance at work and the institution studied could act more actively on consignment margin implications. Finally, it was recommended as the institution's intervention plan formulating courses on financial education and the margin of consignment presented concepts and everyday cases for better assimilation of the employee, through the training program for existing servers in the institution